Two wars and a wedding : a novel [large type] - Willig, Lauren (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"From New York Times bestselling author Lauren Willig comes a dramatic coming of age story with a dual timeline and a single heroine--a bold and adventuring young woman who finds herself caught up in two very different wars on both sides of the Atlantic"--